Analisis Qanun Provinsi Nanggro Aceh Darussalam dalam Kerangka Maqasid Al-Qur’an Negara Kesatuan Republik Indonesia - Nurlia; Abd. Moqsith (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
Nanggroe Aceh Darussalam, one of Indonesia's unique provinces with a 97.26% Muslim population, is governed by the Qanun legal system. The Indonesian province with the highest proportion of Muslims is Aceh. Since the primary goal of the Maqasid Al-Quran is to purify the teachings in the Book of Allah as a guide for living in this world and for continuing to be happy in the hereafter in accordance with the teachings that form the basis of the Al-Quran, this is the reason why the contents of the Qanun Nanggroe Aceh Darussalam primarily implement it. If it is possible for the Nanggroe Aceh Darussalam qanun to become a legal basis in general, the legal framework in the Unitary State of the Republic of Indonesia requires quite serious consideration because, first; Indonesia's religious and cultural diversity, second; principles of a secular and democratic state, third; human rights and individual freedoms, fourth; the need for national unity and harmony, fifth; experiences of other countries with sharia law. it cannot be denied that there will be positive things if this is implemented, including; increasing awareness of law and morality, reducing crime and criminality, encouraging better religious life, respecting Islamic cultural and religious identity, and increasing justice and equality.